(untitled) (Anclajes, 2024)
María Teresa León’s Las peregrinaciones de Teresa is a short story collection published in 1950. This article examines two of its stories from the perspective of the neologism transmemoria, which the author presents in her introduction, with the aim of exploring its critical potential for analyzing the essential meaning of the stories. This allows us to question the use that Hirsch, Young and Bedingfield have made of the concepts of postmemory and transmemory since the early 21st century to highlight the value of the production of “vicarious” discourses about the past by the second generation of exiles and immigrants based on their own reinterpretation of the trauma suffered by their parents. From the analysis of the two narratives and León’s use of the term transmemoria, this article argues for an alternative model of memory in which the resulting narratives have an emancipatory role and in which utopia prevails over trauma and experience over inheritance.